LEGAL PROTECTION FOR COPYRIGHT HOLDERS AGAINST ILLEGAL DISTRIBUTION OF FILMS THROUGH STREAMING SITES - Lira Nova Eliza; Ismail Koto (Inspiring Law Journal, 2026)
This study analyzes the legal protection for copyright holders for the illegal distribution of films through streaming sites from a civil law perspective in Indonesia. The development of information technology and increased internet access have encouraged the widespread distribution of films without permission from copyright holders, which results in economic losses and violations of moral rights as regulated in Law Number 28 of 2014 concerning Copyright. This practice not only impacts creators and broadcasting rights license holders but also has implications for the sustainability of the national film industry, which is protected by Law Number 33 of 2009 concerning Film. This problem demands legal certainty regarding the status of copyright as a property right and a form of legal accountability for violations that occur in the digital space. This study uses a normative legal research method with a statutory and conceptual approach. Data were obtained through a literature study of primary legal materials in the form of Law Number 28 of 2014 concerning Copyright, Law Number 33 of 2009 concerning Film, and the Civil Code, and supported by secondary legal materials in the form of books, journals, and the doctrines of legal experts. The analysis was conducted qualitatively by examining the principles, norms, and legal concepts relevant to the practice of illegal film distribution in the digital era. The results of the study indicate that copyright on film works is an intangible object included in the category of property rights and provides exclusive rights to the creator or copyright holder. The illegal distribution of films through streaming sites fulfills the elements of an unlawful act as regulated in Article 1365 of the Civil Code because it violates the economic rights and moral rights of the creator. Copyright holders have the right to file a civil lawsuit in the form of material and immaterial compensation, termination of unlawful acts, confiscation of the proceeds of violation, and restoration of moral rights through the Commercial Court mechanism. Thus, civil legal protection has a strategic role in ensuring legal certainty, creating justice for copyright holders, and providing a deterrent effect on perpetrators of copyright infringement in the digital realm.